Formulation and Physical-Chemical Analysis of Functional Muffin Made with Inulin, Moringa, and Cacao Adapted for Elderly People with Parkinson's Disease - Paula García-Milla; Rocío Peñalver; Gema Nieto (MDPI AG, 2024)
Parkinson's disease (PD) is a neurodegenerative disorder that affects people's health. Constipation is probably one of the most prominent gastrointestinal symptoms (non-motor symptoms) of PD with devastating consequences. The aim of this research work is to formulate a functional food product, supplemented with inulin, cocoa, and Moringa, which can be an adjuvant in the treatment of constipation. The product was prepared according to a muffin or "Chilean cake" recipe; this basic muffin was prepared with additions of inulin (MI), inulin + cacao (MIC), and inulin + Moringa (MIM). A physical-chemical analysis of the macronutrients and an antioxidant capacity assessment of the samples were conducted, as well as a sensory evaluation performed by a group of people suffering from Parkinson's disease. A statistically significant difference was observed in the soluble (p = 0.0023) and insoluble (p = 0.0015) fiber values between the control samples and all samples. Furthermore, inulin + cacao improved the antioxidant capacity and folate intake compared to the control. Inulin alone has been shown to have antioxidant capacity according to ABTS (262.5728 ± 34.74 μmol TE/g) and DPPH (9.092518 ± 10.43 μmol TE/g) assays. A sensory evaluation showed a preference for the product with inulin and for the product with inulin + cacao, with a 78% purchase intention being reported by the subjects who evaluated the products. The incorporation of inulin and cacao improved the nutritional value of the muffins; the dietary fiber, antioxidant capacity and folate content are some of the features that stood out. A bakery product enriched with inulin, cocoa and Moringa could serve as a nutritional strategy to enhance nutritional value, thus helping in the treatment of constipation.